The Effects of Teacher Modeling and Peers on Religious Behavior among Secondary School Students - Muttaqin, Sopian Kamil; Ibrahim, Cindy Fatikasari; Azizah, Meisya Nur; Hasbulloh, Muhammad Fikri (Universitas Al-Amien Prenduan, 2025)
Students’ religious behavior in the modern era faces serious challenges due to modernization, cultural globalization, and rising individualism. This study examines the influence of teacher modeling and peer influence on the religious behavior of public secondary school students in Bandung, West Java, Indonesia. Using a quantitative correlational–explanatory design, data were collected from 138 eighth- and ninth-grade students and analyzed using Pearson correlation and multiple linear regression (SPSS 29). The findings show (1) no significant differences in religious behavior based on gender (p = 0.361), (2) a moderate positive relationship between teacher modeling and students’ religious behavior (r = 0.461; p < 0.001), and (3) a moderate positive relationship between peer influence and students’ religious behavior (r = 0.524; p < 0.001). Regression analysis further demonstrates that teacher modeling accounts for 26.8% (? = 0.268) and peer influence accounts for 39.3% (? = 0.393) of the variance in students’ religious behavior. Importantly, the results describe how these influences occur. Teacher modeling operates through Bandura’s observational learning processes—attention, retention, behavioral reproduction, and motivation—in which students internalize teachers’ demonstrated religious practices and ethical conduct. Meanwhile, peers shape students’ religious behavior through mechanisms of social interaction, shared norms, and emotional support, reinforcing daily religious practices across Al-Ghaz?l?’s core domains of worship, morality, and social conduct.